Biofilm formation by Listeria monocytogenes on stainless steel surface and biotransfer potential - Oliveira,Maíra Maciel Mattos de (2010)
An experimental model was proposed to study biofilm formation by Listeria monocytogenes ATCC 19117 on AISI 304 (#4) stainless steel surface and biotransfer potential during this process. In this model, biofilm formation was conducted on the surface of stainless steel coupons, set on a stainless steel base with 4 divisions, each one supporting 21 coupons. Trypic Soy Broth was used as bacterial growth substrate, with incubation at 37 ºC and stirring of 50 rpm. The number of adhered cells was determined after 3, 48, 96, 144, 192 and 240 hours of biofilm formation and biotransfer potential from 96 hours. Stainless steel coupons were submitted to Scanning Electron Microscopy (SEM) after 3, 144 and 240 hours. Based on the number of adhered cells and SEM, it was observed that L. monocytogenes adhered rapidly to the stainless steel surface, with mature biofilm being formed after 240 hours. The biotransfer potential of bacterium to substrate occurred at all the stages analyzed. The rapid capacity of adhesion to surface, combined with biotransfer potential throughout the biofilm formation stages, make L. monocytogenes a potential risk to the food industry. Both the experimental model developed and the methodology used were efficient in the study of biofilm formation by L. monocytogenes on stainless steel surface and biotransfer potential.